Analisis Pemasaran Komoditi Cabai Rawit Capsicum Frutescens di Kecamatan Remboken Kabupaten Minahasa (Marketing Analysis Of Chilli Capsicum Frutescens Commodity in Remboken Sub-District, Minahasa Regency North Sulawesi Province) - nFN Hasnal; Lyndon R. J. Pangemanan; Caroline B. D. Pakasi (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2022)
The objective of this research is to analyze the efficiency of marketing channels and institutions for cayenne pepper commodities in Remboken District. The data used in this study are primary data and secondary data. The sampling technique in this study was purposive sampling and snowball sampling. The number of samples of Farmers is 40 respondents, Collector Traders are 5 respondents and Retailers are 17 respondents. This study uses questionnaires and interviews to describe the pattern of cayenne pepper marketing channels in Remboken District, which is then described. The data analysis method used is the analysis of Marketing Margin, Farmer's Share and Marketing Efficiency. The research results showed that the marketing channel pattern for the commodity of cayenne pepper in Remboken District contained three channels, namely: Marketing Channel 1: Farmers – Consumers; 2: Farmers – Retailers – Consumers; 3: Farmers – Collectors – Retailers – Consumers. The lowest margin in marketing channel I was 0, Farmer Share was 98%, this is because farmers sell directly to consumers. and the smallest percentage of Marketing Efficiency is in channel I, which is 1.70%, this is because the costs incurred by marketing channel I are smaller than marketing channels II and III.